The skills required of university students in the 4.0 era - Lê Thị Duyên (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The Industrial revolution 4.0 has changed, and drastically impacted all areas of the country’s economic and social life. It opens up many opportunities, but also poses many challenges. In order to integrate anh succeed in the 4.0 era, in addition to professional qualifications, students need to have skills, not only foreign language skills, information and communication technology skills, but also creative skills, critical thinking skills, communication skills, problem solving skills,...Every student must constantly study, practice, and strive to be better anh more excellent if they do not want to be replaced and eliminated from work in the 4.0 era.